Theoria-Unendlichkeit-Aufstieg : philosophische Implikationen zu "De vita Moysis" von Gregor von Nyssa - Böhm, Thomas. (Vigiliae Christianae, Supplements, 1996)
The relationship between theology and philosophy in Gregory of Nyssa's thought is a subject of great controversy. This study on one of Gregory's key writings does not however focus on the study of the source material, but discusses instead the philosophical implications of Gregory's ideas. Thus it is possible to place Gregory's principles in a broader context while maintaining the differences with philosophy. In the first part of the work, the Prooemium of the De Vita Moysis is examined. Following the classical rhetorical tradition, Gregory here starts off with the central themes of the entire work. The second part is devoted to the concept of theoria . This is explored through discussions of the eternity of God, \'language theory\', human striving towards God, and biblical interpretation. In the last chapter these structures of the notion of theoria are further examined in the light of the theophany in the De Vita Moysis .